1982
DOI: 10.2307/1589886
|View full text |Cite
|
Sign up to set email alerts
|

Serotypes of Avian Infectious Bronchitis Virus Isolates from Field Cases in Japan

Abstract: Eight etiologic agents isolated from field cases in Japan were identified as isolates of infectious bronchitis virus by agar-gel diffusion, buoyant-density determination on sucrose-density centrifugation, and morphological study by electron microscope of the purified viruses. In studies of the antigenic relationships of the eight isolates and six known infectious bronchitis viruses, antigenic diversity of these viruses was recognized from the degrees of relatedness using a plaque reduction in the "constant-vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…It is suggested that Korean IBVs are continually evolving (Jang et al, 2007). Doi et al (1982) studied the antigenic relationship of eight Japanese IBV isolates obtained between 1960 and 1974 and concluded that there were many distinct serotypes of IBV in Japan. Mase et al (2004) carried out a detailed analysis of Japanese IBV variants by looking at the N-terminus of the S1 glycoprotein and identified three major genetic groups not found in other countries.…”
Section: Asiamentioning
confidence: 99%
“…It is suggested that Korean IBVs are continually evolving (Jang et al, 2007). Doi et al (1982) studied the antigenic relationship of eight Japanese IBV isolates obtained between 1960 and 1974 and concluded that there were many distinct serotypes of IBV in Japan. Mase et al (2004) carried out a detailed analysis of Japanese IBV variants by looking at the N-terminus of the S1 glycoprotein and identified three major genetic groups not found in other countries.…”
Section: Asiamentioning
confidence: 99%
“…The disagreement between respiratory signs and tracheal virus recovery in chickens vaccinated with the H-120 strain (Experiment 3) was due to the long interval between vaccination and challenge or to weak cross-reactivity between the vaccination strain (H-120) and the challenge strain (Kita-1/Tokushima). The H-120 strain should be assessed for its protective ability against different serotypes of Japanese field IBV (Doi et al, 1983), because it is frequently employed as an IB vaccine in the field.…”
Section: Relationship Between Serum Hi Antibody Litres and Criteria Omentioning
confidence: 99%
“…Until now some 20 serotypes, basically defined by cross-neutralization tests, have been found. Most of them have a worldwide distribution (Dawson & Gough, 1971 ;Lohr, 1976;Doi et al, 1982;Locher et al, 1983a, b;Cook, 1984). In some cases unequivocal assignment to a serotype of an isolate is complicated by the phenomenon of one-way neutralization : a serum against strain A neutralizes strain B but the antiserum against strain B does not neutralize strain A (Dawson & Gough, 1971 ;Locher et al, 1983a, b).…”
Section: Introductionmentioning
confidence: 99%